Suitability Analysis for Waste Disposal Site Using GIS Based Multi-Criteria Decision Analysis: A Case Study of Jhapa District, Nepal - Poudel, Hemanta; Ghimire, Sujan; Upadhyaya, Sharad (Nepal Journal of Multidisciplinary Research, 2023)
Environmental degradation resulting from rapid urbanization, industrialization, and overpopulation has become a critical global issue, primarily due to the generation of vast amounts of solid waste. Effective solid waste management and proper disposal arrangements are imperative to mitigate the adverse impacts on the environment. This research article focuses on identifying an appropriate waste disposal site for efficient waste management and dumping. Jhapa district in Nepal is chosen as the study area due to its diverse settlement zones, including industrial and commercial regions. To achieve this goal, Geographic Information based Multi-Criteria Decision Analysis (MCDA) method is used. The outcome of this project is a suitability model that categorizes different areas as least suitable, suitable, more suitable, and most suitable for establishing a waste disposal site. By considering multiple criteria, including environmental, health, residential and political factors, and the model provides a comprehensive assessment of potential sites. This research contributes to the field of waste management and environmental sustainability by offering a practical approach to decision-making in waste disposal site selection, promoting a healthier and cleaner environment for the residents of Jhapa district and beyond.